(untitled) (Eurasian Scientific Herald, 2023)
The article examines the theoretical and methodological basis of the processes associated with the problems of increasing the competitiveness of the textile industry in the context of structural changes in the national economy. The existing shortcomings in this regard and their impact on the competitiveness of the textile industry have been assessed. According to the results of the analysis, scientific proposals and practical recommendations aimed at overcoming the problems of increasing the competitiveness of the textile industry in the context of structural changes have been formed